151 Groin-Hematoma in Patients Undergoing Manual Compression Following Sheath Pull. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Chandra, Arun; Jiang, Bowen; Bender, Matthew; Campos, Jessica K; Zarrin, David A; Vo, Chau D; Young, Robert W.C; Caplan, Justin; Huang, Judy; Tamargo, Rafael J; Lin, Li-Mei; Colby, Geoffrey P; et al.
Abstract: INTRODUCTION: Vascular access-site complications are an important cause of morbidity among individuals undergoing endovascular procedures. Closure devices such as Mynx or Angioseal shorten times needed for hemostasis and are comfortable for patients. However, the safety of such closure devices remains in question as they may lead to infection and hematoma. In our institution we routinely monitor complications in patients undergoing manual compression following sheath pull. Here we aim to summarize clinical results of manual compression with special attention to the prevalence of groin hematoma in these patients. METHODS: Retrospective patient database review from August 2011 to November 2017 revealed that there were 810 patients at our institution who underwent manual compression following sheath pull. Sheaths are pulled 4 h after procedure or on POD1 if systemic heparin is needed. All patients underwent endovascular embolization with pipeline and 8 Fr sheath access. Clinical outcomes of these patients including prevalence of groin hematoma, infection, and length of stay (LOS) were retrospectively collected and statistically analyzed. P values less < .05 were set as statistical significance. RESULTS: Baseline characteristics and operative data were as follows: average age 56, gender (female) 81%. All patients had manual compression following sheath pull. The prevalence of groin hematoma in this group is 2.7%. This is much lower than the literature reported hematoma complication rate for closure devices which ranges between 5 and 10%. The prevalence of infection in this group was 0.5%. This is lower than the literature reported infection rate of up to 5.1% for closure devices. In addition, the average LOS in patients with hematoma post sheath was 5.6 d, while 2.3 d in patients without hematoma. CONCLUSION: In comparison to closure devices, manual compression post sheath pull has a lower risk of groin hematoma and infection. The longer LOS shows that groin hematoma is not a benign complication and further enforces our institutional standards for low hematoma rates via manual compression.